A novel cytosolic class I antigen-processing pathway for endoplasmic-reticulum-targeted proteins. - Schlosser, E; Otero, C; Wuensch, C; Kessler, B; Edelmann, M; Brunisholz, R; Drexler, I; Legler, D; Groettrup, M (2007)
Proteins bearing an endoplasmic reticulum (ER) leader are inserted into the ER followed by cleavage of the signal peptide. Major histocompatibility complex class I-restricted T-cell epitopes can be generated from these proteins by the proteasome after retrotranslocation into the cytosol. Here, we show that an HLA-A(*)0201-restricted epitope from prostate stem cell antigen contains the cleavage site of the ER signal peptidase. The resulting cleavage products fail to bind to HLA-A(*)0201 and are not recognized by T lymphocytes. As processing of prostate stem cell antigen by signal peptidase occurs immediately after co-translational insertion, the epitope must be processed from polypeptides that have never reached the ER. The processing of this epitope depends on the proteasome and the transporter associated with antigen processing and shows a novel pathway of class I processing that relies on the failure of ER-targeted proteins to reach their target compartment.